Fontes orgânicas, polímero hidroabsorvente e fertilizante organomineral na aclimatação de mudas de cultivares de abacaxizeiro - Mendonça, Luciana Freitas de Medeiros (Universidade Federal Rural do Semi-Árido, 2016)
Micropropagation can be an alternative for spreading pineapples cultivars. Although this technique offers many advantages, there are difficulties on the rooting and slow growth of pineapple seedlings, which requires a long period of acclimatization in green house. The main purpose of this study was to evaluate organic sources, such as hydrogel polymer and doses of organo-mineral fertilizer in pineapple seedlings during acclimatization. Experiment 1: The first experiment was conducted on the greenhouse placed on the east campus of the Universidade Federal Rural do Semi-Árido (UFERSA), located in Mossoró/RN. The experiment was conducted in randomized blocks in a 2x2x3 factorial design, 2 pineapple cultivars (Imperial and Vitoria), 2 uses for hydrogel (with and without its use on the substrate) and 3tested organic sources (cattle and goat manure, as well as organic source), a total of 12 treatments with 4 replications and 5 seedlings per plot. The data obtained were submitted to analysis of variance, according to the factorial scheme adopted, and the main averages compared through Scott-Knott testat 5%.Experiment 2: The second experiment was also conducted in the greenhouse placed on the east campus of the Universidade Federal Rural do Semi-Árido (UFERSA), located in Mossoró/RN. The experiment was performed in randomized blocks in a 2x5 factorial design, 2 pineapple cultivars (Imperial e Vitoria) and 5 doses of organo-mineral fertilizer (0;2.5; 5; 7.5 and 10g), a total of10 treatments with 4 replications and 5 seedlings per plot. The statistical analysis was assisted by software tools, and the qualitative data means compared through Scott-Knott testat 5%while the quantitative data was submitted to regression analysis and the mathematical models were adjusted with the help of the Table Curve software with a significance for the T test (p<0.05) for the equation parameters. The cattle and goat manure were the organic sources providing improvement on the growth characteristics in both cultivars; the cattle manure also provided more nutritional benefits for the seedlings; the use of hydrogel did not favor the growth of the aerial part of cultivars, but it contributed for the weight increase of the root system dry mass when mixed with the cattle manure in both cultivars. After 270 days of acclimatization, the pineapple cultivar Imperial showed more efficiency with the macronutrient retention in the seedling leaves. The doses of organo-mineral fertilizer that provided more improvement in the biometrical characteristics were 10g and 5g for both ‘Vitoria’ and ‘Imperial’, respectively. Using growing doses of the phosphate soil conditioning, both cultivars showed similar foliar levels for P and Mg. For the cultivar Imperial, the phosphate fertilizer provided more improvement on the foliar levels for K and Ca. However, for the cultivar Vitoria only the Ca level was affected by the growing doses
Keywords: Fruticultura; Ananas comosus; Propagação; Fruits; Ananas comosus; Propagation; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA